Report of the successful Senning procedure from Nepal - Timala, Rabindra B.; Aryal, Marisha; Parajuli, Santosh; Pradhan, Rupak; Joshi, Rheecha; Rajbhandari, Nivesh; Basnet, Nishes; Gautam, Navin (Nepalese Heart Journal, 2023)
A child born with transposition of great arteries should undergo arterial switch, preferably within 2 to 3 weeks of life. Sometimes, this can be extended even up to 2 months of life, if left ventricular mass is adequate. When child presents very late left ventricle may have regressed, so the options left is either left ventricular training and arterial switch or atrial switch. We present here, a 3 years old child presenting with transposition of great arteries, who underwent successful Senning procedure.